(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
This is difficult to ignore the waste of food at big events, banquets, and hotels when so many poorer communities are fighting hunger. The Smart Food Saver Solution The Smart Food Saver is a mobile based platform that reduces the mismatch by redirecting excess food from events to orphanages and senior citizen homes. The platform allows hotels and event organizers to register excess food, and NGOs and volunteers in the vicinity receive instant alerts to collect and distribute. Built-in GPS location, food quantity registration, and time-based notification help you deliver fresh and safe foods. By bridging the gap between donors and recipients digitally, the application enhances sustainability, prevents food wastage, and encourages the welfare of the community. The initiative shows how even simple technology can build social responsibility and a fairer society